Test of Equity Valuation to Predict Market Price by Using Multiples Valuation: Evidence from Indonesia - , IGNATIUS TEGUH PRAYOGA; , Prof. Dr. Jogiyanto Hartono, MBA, Ak. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research is analyzing the accuracy of relative (multiples) valuation method to predict market price in Indonesia Stock Exchange especially in equity multiples. Those value drivers that are being assessed are earning-per-share, book-value-per-share, cash-flow-per-share, and sales-per-share. The method that is being used for this research is by determining the Root Mean Square Error (RMSE) of each value driver. This research finds that the earning-per-share results the lowest RMSE among all value drivers which indicates that EPS is the most accurate value driver for valuation by using relative (multiples) method in Indonesia Stock Exchange.